Investigating the use of video gaming technologies in enhancing language skills of FL students - Khasawneh, Mohamad Ahmad Saleem (Research Journal in Advanced Humanities, 2024)
The current globalized language learning system has been characterized by innovative learning methods. Among these innovative methods is the use of video gaming technological tools. Video gaming technological tools have proven to aid learners, including novices in learning any language of their choice. However, this work is dedicated to exploring the roles video games play tools in improving the language proficiency of foreign language students. Nevertheless, a mixed methodology was adopted in this study to achieve the main goal of this research. On the other hand, among the fifty-seven individuals who participated in this study, fifty-three of them were used for the quantitative survey, while the remaining four, participated in the interview. The findings of this study show that video games are great resources for language learning. The study uncovered that video games can be used as foundational language-learning material for those who are new to a particular language. In regards to the role video games play in language proficiency improvement, it was observed that video games help to develop various language skills of foreign language learners such as speaking and writing among others. These videos also motivate, create a conducive environment for language learning, engage, and enable language learners to learn language easily. Despite the factors that hinder the effective utilization of these video games, it was observed that some of these challenges are less than the benefits of using this tool. Apart from motivating and engaging the students, the potentials of the utilization of video games for language learning prove to be more effective when used as augmentative tools. Hence, the research recommends a proper integration of video games in the classroom by language teachers.